The first bilateral investment treaties : U.S. postwar friendship, commerce, and navigation treaties - Vandevelde, Kenneth J. (New York, NY : Oxford University Press, 2017)
This work provides a history of the U.S. postwar Friendship, Commerce, and Navigation (FCN) treaty program, and focuses on the investment-related provisions of those treaties. The author explains the original understanding of the language of this vast network of agreements which have been and continue to be the subject of hundreds of international arbitrations and billions of dollars in claims. It is based on a review of some 32,000 pages of negotiating history housed in the National Archives.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 16, 2017).
Keywords: United States -- Foreign relations -- Treaties; Investments, Foreign -- Law and legislation -- United States; United States -- Commercial treaties; International and municipal law -- United States; Law; Laws of specific jurisdictions & specific areas of law